SHEEHAN SYNDROME MANIFESTING AS MIXED ADRENAL AND MYXEDEMA CRISIS:: A RARE CASE - Waafi , Affa Kiysa (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Sheehan syndrome rarely arises as a complication of postpartum hemorrhage with the advancement in obstetric management. We present a 36-year-old Indonesian female with shock, bradycardia, refractory hypoglycemia, a and 3-day history of fever, productive cough, and vomiting. She had a puffy face and a muffled heart sound. With a history of massive postpartum bleeding 1 year ago and amenorrhea since then, she was presumed to have hypopituitarism manifesting as adrenal and myxedema crisis precipitated by infection. Additional examination showed anemia, hyponatremia, and decreased levels of TSH, prolactin, LH, FSH, cortisol, estradiol, and progesterone. Her pituitary MRI showed a marked decrease in the gland size. The condition of the patient improved with proper management of infection and prompt hormone replacement. This case emphasizes the need for awareness about Sheehan syndrome which could potentially result in a grave prognosis with delayed management, especially among physicians working in developing countries with limited healthcare facilities.